2018
DOI: 10.17943/etku.366193
|View full text |Cite
|
Sign up to set email alerts
|

ÖĞRETMEN ADAYLARININ ROBOTİK PROGRAMLAMADA AKIŞ, KAYGI ve BİLİŞSEL YÜK SEVİYELERİ

Abstract: The aim of this study was to compare pre-service teachers’ flow experience, anxiety and cognitive loads in the process of robotics programming, based on whether they were experienced or inexperienced. The sample of the study consisted of 19 pre-service teachers (16 females, 3 males) from different specialties. Within the scope of the study, pre-service teachers carried out five robotics programming activities. Two of these activities were grouped as beginner level and three as experience-requiring activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Studies that are to be practiced or expected to be practiced regarding robotics and coding at schools might be seen as a difficult, challenging process for teachers. However, at the end of studies they carried, it was observed that this kind of anxiety has disappear, the information chaos that constitutes fear has decreased and they have carried practices in an enjoyable manner as teachers gain experience (Kay & Moss, 2012;Şişman & Küçük, 2018). Therefore, that experienced teachers take part constituting school ecosystem and at the same time, it is an important issue that these teachers support educationally in order to carry out robotic-coding studies with their students in or out of the class.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that are to be practiced or expected to be practiced regarding robotics and coding at schools might be seen as a difficult, challenging process for teachers. However, at the end of studies they carried, it was observed that this kind of anxiety has disappear, the information chaos that constitutes fear has decreased and they have carried practices in an enjoyable manner as teachers gain experience (Kay & Moss, 2012;Şişman & Küçük, 2018). Therefore, that experienced teachers take part constituting school ecosystem and at the same time, it is an important issue that these teachers support educationally in order to carry out robotic-coding studies with their students in or out of the class.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of increasing the cognitive load by presenting the whole process to the students at once, dividing the process into meaningful parts, for example first presenting the parts and then presenting the relations of the parts with each other in the whole process will decrease the cognitive load. For example, if a robot that moves without the obstacles is to be programmed, it is possible to implement a holistic programming application that consists of meaningful parts such as moving the motor, receiving data from the sensor, looping and decision structure (Sisman & Kucuk, 2018). Robotics programming contributes to creative design, computational thinking and problem-solving skill development (Bers, 2010;Karim, Lemaignan & Mondada, 2015).…”
Section: Introductionmentioning
confidence: 99%